Atypical presentation of isolated orbital Langerhans cell histiocytosis - Richards, Nikisha Q; Young, Matthew; Pierson, Kasey; Le, John; Rong, Yuan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: A 9-year old female presented with one month of waxing and waning upper eyelid swelling. An excisional biopsy via anterior orbitotomy was performed. Objective: To describe a patient presenting atypically with symptoms concerning for orbital cellulitis who was diagnosed with Langerhans cell histiocytosis (LCH). Methods: Description of case report. Results: We report a case of a 9-year old female with one month of periorbital edema and erythema suspected to be orbital cellulitis. A complete ophthalmological exam, subsequent imaging, and an excisional biopsy revealed the diagnosis of LCH. With a confirmed diagnosis, the patient started chemotherapy indicated by the Histiocyte Society Evaluation and Treatment Guidelines. Conclusion: Langerhans cell histiocytosis (LCH) embodies a spectrum of diseases with the primary pathologic process being the abnormal proliferation of polyclonal Langerhans cells. In children with isolated bony involvement, the most common presenting symptom is pain. Rarely is orbital involvement with associated periorbital edema and erythema the primary presentation.